Dy3+/Tb3+-codoped tunable warm light-emitting fluorogermanate glass phosphor - Alves, Rafaela T.; Trindade, Camyla M.; Santos, Weslley Q.; Gouveia-Neto, Artur S.; Bueno, Luciano A.; Mathias, Caio F. [UNESP]; Nalin, Marcelo [UNESP] (SPIE, the international society for optics and photonics, 2016)
Polychromatic tunable visible light emission in the region of the low correlated color temperature range using Dy3+/Tb3+ codoped PbGeO3:PbF2:CdF2 glass phosphor under UV-blue LED light excitation is presented. The glass phosphor was synthesized and the light emission feature was examined under UV-blue (353, 375, 385, and 405 nm) excitation. Emission around 484, 573, 663, and 754 nm due to dysprosium, and 488, 545, 585, 620, and 690 nm owing to terbium ions, was observed and analyzed as a function of the dysprosium and terbium contents and excitation wavelength. The excitation spectrum was examined and showed resonance peaks around 385 nm for the 573-nm emission of Dy3+, and 375 nm for the 545 nm of Tb3+. Energy-transfer process from Dy3+(F49/2) to Tb3+(D54) was also observed. Results indicated that the polychromatic visible light emitter herein reported produced light possessing tunable color tone via excitation wavelength and ions' mass ratio. The tint of the tunable overall emission resided in the warm region of the white-light boundary of the CIE-1931 chromaticity diagram.
Keywords: Phosphor; polychromatic; rare-earth; solid-state-lightining; warm-light; white-light emitting diode